(untitled) (Journal of Economic Research & Business Administration, 2021)
Infrastructure services are not only crucial for enhancing the welfare of the people but to also foster economic growth and development. Despite these essential services, there is a glaring infrastructure gaps in Sub-Saharan Africa more than any other region in the world. In the light of this and measurement problems associated with infrastructure development, it is therefore necessary to highlight the state of infrastructure development in SSA. This study examines the state of infrastructure development in SSA by considering 43 nations over the period of 2000 to 2018. Infrastructure development was proxied by the composite infrastructure index which include both the physical and social infrastructure. The study employed Principal Components Analysis (PCA) in building the aggregate or composite index, and descriptive statistics, stylized facts and correlation analysis were employed for the analysis of the data. Findings from this study reveal that infrastructural development has improved significantly in SSA for the period of study even though this is very low compare to the development attained in other regions of the world, and most of the improvement are from physical infrastructure, most especially telecommunication sector, and to a lesser degree, in health and water infrastructure. The study therefore recommends that stakeholders should engage in policies design that will improve infrastructure development in SSA most especially for the low income countries as majority of them were found at the bottom of ranking. This will help in closing the wide gap of inequality in access to infrastructure services among the SSA countries and other developing countries in other regions of the world. Key words: Infrastructure development, Composite Infrastructure Index, Principal Components Analysis, Physical and Social Infrastructure.